A Study of Corrolink Structural Insulated Panel (SIP) to Windborne Debris Impacts - Chen, Wensu; Hao, Hong (Trans Tech Publications, 2015)
Structural insulated panel (SIP) is considered as a green panel in construction industry because of the low thermal conductivity of the sandwiched EPS core (i.e extended polystyrene). It is a lightweight composite structure and is widely used in commercial, industrial and residential buildings to construct the building envelop including roof and wall. The windborne debris driven by cyclone or hurricane usually imposes intensive localized impact on the structural panel, which might create opening to the structure. The opening on the building envelope might cause internal pressures increase and result in substantial damage to the building structures, such as roof lifting up and wall collapse. The Australian Wind Loading Code (version 2011) [1] requires structural panels to resist projectile debris impact at a velocity equal to 40% of the wind speed, which could be more than 40 m/s in the tropical area with the wind speed more than 100m/s. In this study, two kinds of SIP under projectile debris impact were investigated, i.e. “Corrolink” and “Double-corrolink” composite panels shown in Fig. 1. Laboratory tests were carried out by using pneumatic cannon testing system to investigate the dynamic response of composite panels subjected to wooden projectile impacts. The failure modes were observed. The structural dynamic responses were also examined quantitatively based on the deformation and strain time histories measured in the tests. The penetration resistance capacity of panels subjected to windborne debris impact was assessed.